Autoimmune Cytopenias Developing Late Post Alemtuzumab-Based Allogeneic Stem Cell Transplantation: Presentation of Short Case Series from a Transplant Center. (14th August 2020) - Lloyd, Rebecca; Nikolousis, Emmanouil; Kishore, Bhuvan; Lovell, Richard; Shankara, Paneesha; Zeid, Nervana Abou; Horgan, Claire; Panteliadou, Alkistis Kyra; McIlroy, Graham; Xenou, Evgenia; Kaparou, Maria; Holder, Kathleen; et al.
Stem cell transplantation remains the curative option for many patients with hematological malignancies. The long-term effects of these treatments on the patients and their immune systems have been extensively investigated, but there remains a paucity of data regarding autoimmune manifestations post-transplant, although these effects are well recognized. Herein we present the clinical picture and therapeutic approach in three patients (cases 1–3), with varied presentations of autoimmune disease post-transplant. Case 1 exhibited autoimmune hemolytic anemia and other autoimmune manifestations (serositis, thyroiditis), that were probably linked to graft versus relapsed leukemia effect. Cases 2 and 3 had pure red white cell aplasia and pure red cell aplasia, respectively, which were associated with hyperglobulinemia and a clonal T cell expansion.